Thin layer drying characteristics and its influence on the physical properties and bioactive compounds of Misai Kucing plant (Orthosiphon staminues) leaves
O. stamineus or locally known as misai kucing is a Malaysian herbal plant, popular as a traditional medicine especially in the Southeast Asian region. It is believed to treat urinary tract diseases, kidney stones and many other human illnesses. Since this herb is stored and consumed in its dried form, knowledge of thin layer drying characteristics is important. The thin layer drying characteristics studies included moisture sorption behavior, drying kinetics and effects of drying conditions on final quality of O. stamineus leaves. Adequate knowledge of the drying characteristics provides appropriate final samples moisture content, thus decreases drying time, mass losses, risk of quality degradation, and reduces energy consumptions. In this work, the moisture sorption behavior was studied by developing moisture sorption isotherms at temperatures of 5 oC and ambient (about 30 oC) and at 5 levels of relative humidity ranging from 11.3 % to 75.7 % by a static gravimetric method. The thin layer drying characteristics of O. stamineus were evaluated at temperatures of 30, 40 and 50 oC and at air velocities of 0.8 and 1.3 m/s using a fabricated laboratory scale hot air dryer. A mathematical modeling was performed using a statistical software package to compare experimental data with predicted data for both moisture sorption isotherms and drying kinetics. Five widely used moisture sorption models, namely Oswin, Peleg, Guggenheim-Anderson-de-Boer (GAB), Brunauer, Emmett, & Teller (BET) and Chung & Pfost models and seven widely used thin layer drying models, namely Lewis, Page, Modified Page, Handerson & Pabis, Midili & Kucuk, Two Term Exponential and Wang & Singh were chosen. Color quality, total phenolic content and biomarker compounds (i.e. RA, SEN and TMF) concentration were determined to represent the final dried leaves quality. The moisture sorption isotherms of O. stamineus were found to be of Type III isotherm (J-shaped).The comparison between the experimental data and the predicted data of the moisture sorption isotherms was found to be closely followed the Peleg model, whereas, the thin layer drying kinetics closed to the Midili & Kucuk model. The thin layer drying of O. stamineus leaves took place in a falling rate period only.